2019
DOI: 10.1037/bne0000344
|View full text |Cite
|
Sign up to set email alerts
|

Lesions to the lateral mammillary nuclei disrupt spatial learning in rats.

Abstract: The head direction (HD) signal is thought to originate in the reciprocal connections between the dorsal tegmental nuclei (DTN) and the lateral mammillary nuclei (LMN) and lesions to these structures disrupt the HD signal in downstream structures. Lesions to the DTN also disrupt performance on spatial tasks where directional heading is thought to be important. In Experiment 1, rats with bilateral electrolytic lesions of the LMN and sham controls were trained on 2 tasks previously shown to be sensitive to DTN da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Undersampled Nyquist frequencies can alias into the measured fMRI signal and drive hypothalamic 'synchronous' activity in the presence of suppressed cortical connectivity strength. However, despite this possible non-neuronal mechanism there are studies that have observed a role for hypothalamic nuclei in functional connectivity in models of pain, in human studies of migraine headache, and in studies of obesity where increases in hypothalamic functional connectivity have been reported [62][63][64] .…”
Section: Discussionmentioning
confidence: 99%
“…Undersampled Nyquist frequencies can alias into the measured fMRI signal and drive hypothalamic 'synchronous' activity in the presence of suppressed cortical connectivity strength. However, despite this possible non-neuronal mechanism there are studies that have observed a role for hypothalamic nuclei in functional connectivity in models of pain, in human studies of migraine headache, and in studies of obesity where increases in hypothalamic functional connectivity have been reported [62][63][64] .…”
Section: Discussionmentioning
confidence: 99%
“…Nyquist frequencies can alias into the measured fMRI signal and drive hypothalamic 'synchronous' activity in the presence of suppressed cortical connectivity strength. However, despite this possible non-neuronal mechanism there are studies that have observed a role for hypothalamic nuclei in functional connectivity in models of pain, in human studies of migraine headache, and in studies of obesity where increases in hypothalamic functional connectivity have been reported (83)(84)(85).…”
Section: Discussionmentioning
confidence: 99%